Manufacturing of the ISO 25178-70 material measures with direct laser writing: a feasibility study. (21st May 2018) - Eifler, M; Hering, J; von Freymann, G; Seewig, J
Abstract: The standard ISO 25178-70 defines material measures for the calibration of 2D- and 3D-topography measurement devices. Some of the suggested material measures are established within the industrial application for a long time while others have not yet been extensively researched regarding their practical abilities. This paper describes a holistic and systematic investigation of the ISO 25178-70 material measures. The manufacturing of the suggested geometries is executed with two-photon laser lithography, alias direct laser writing (DLW). Since this manufacturing process is not yet frequently used in a material measures context, it is examined regarding its suitability for the fabrication of the ISO 25178-70 material measures. With DLW, it is possible to manufacture multiple material measures on one sample in order to enable a comprehensive calibration of optical topography measurement devices. The manufactured ISO 25178-70 geometries are examined using different 3D-topography measuring devices. In doing so, their abilities regarding the calibration of the devices can be evaluated and the practical feasibility of their industrial application is assessed. For the review of this practical usefulness, varying calibration and evaluation strategies are taken into account.